BENDA MANIPULATIF DARI SANDAL JEPIT DAN PELEPAH RUMBIA UNTUK PEMAHAMAN KONSEP ALJABAR SISWA KELAS VIII SMP - Fachrurazi fachrurazi. (Universitas Syiah Kuala, 2018)
Student difficulties in understanding algebra particularly in factoring is because teachers have not been able to utilize manipulative objects (props) as a medium to narrow nature of mathematical abstraction itself. Props mathematics is a concrete object that can be manipulated, in order to bridge mathematical abstraction. Flip-flops and frond thatch are two things that will serve as a manipulative object in learning algebra. The purpose of this study are: (1) to describe the use of flip-flops and frond thatch as manipulative objects to enhance the ability algebra of junior high school students; and (2) To know the use of manipulative objects flip-flops and frond thatch will reach or not the ability algebra of junior high school reached an average of more than 65. This study is a quantitative study with experimental method. In this study there is only one group of research subjects derived from the 3 school level (low, medium, and high), the experimental group doing mathematics by using manipulative objects. To determine the ability of an algebraic increase to more than 65 will be used t-test. The result showed that the tcount ttable (5:44 1.67), so in this case H0 is rejected. Further in the learning process was also found that the students are very easy in factoring a quadratic equation by using the manipulative objects. The conclusions of this study are: (1) Learning with the use of flip-flops and sago palm frond as manipulative objects to the increased ability of algebra junior high school students has been going well and facilitate student. (2) Learning mathematics algebra material using props from the flip-flops and frond thatch can improve the understanding of junior high school eighth grade on the material algebra reaches an average (μ0) of more than 65.